Determination of Optimal Conditions for Separation of Metal Ions Through Membrane Dialysis/Electrodialysis Using Statistical Experimental Methods - Wang, Jau-Kai; Char, Jir-Ming; Huang, Ting-Chia (IntechOpen, 2011)
None